A novel model of photoacoustic and thermalelectronic waves in semiconductor material - M. H. Raddadi; Kh. Lotfy; A. A. El-Bary; A. M. S. Mahdy; E. S. Elidy (AIP Advances)
We explore theoretically the photoacoustic wave propagation created by the photoexcited carrier diffusion in the thermoelastic domain. Consideration is given to the coupling of acoustic and thermomechanical waves. Under the influence of photothermal and thermoelasticity theories, the governing equations are derived. The photoacoustic wave creation is independent of the electron–phonon and electron–hole thermalization and results from the thermoelastic stress brought on by the increase in temperature generated by the light. Considering the optical, elastic, and thermoelastic properties of semiconductor material, photoacoustic signals are predicted by solving a thermal diffusion issue and then a thermoelastic problem in sequence. Using the harmonic wave method, we can solve the mathematical model. All the physical fields in the physical domain can be obtained from the numerical solutions of the mathematical model, including displacements, temperature, acoustic pressure, mechanical distributions, and carrier density diffusion. Two- and three-dimensional (2D and 3D) graphical representations of the thermoelectric, thermo-energy, and thermoelastic parameters are created, and their impacts are compared and analyzed.